The Fundamental Forces and Their Unification (Global Journal of Science Frontier Research, 2025)
This paper introduces the concept of unity, defined as matter or a system with its maximum energy limit. Unity is proposed as the origin of inertia and mass due to its resistance to change. Unity force is defined as matter's tendency of being unity, expressed as attracting while energy sharing in a unity or repelling while excess-energy releasing out of the unity. Mass is a special case of unity force: when in unity, matter's unity force Fu equals its rest mass M: Fu = M. The statement that matter has mass and energy means that matter has a unity force using its energy to maintain its unity. Matter's unity force Fu also equals its weight with its unity centre Wu: Fu = Wu. Unity force is proposed as the fundamental force underlying all known natural forces. Strong force and weak force are the same unity force, with every two protons sharing energy with one electron in atomic nuclei in their respective situations. Electromagnetism results from electron waves releasing excess-energy for dynamic unity that can be aligned and intensified by outside forces. Unity force is also proposed to replace gravity. The paper also challenges certain misconceptions in contemporary physics.
Keywords: matter; mass and energy; energy limit; energy sharing; excess-energy releasing; unity